Implementasi Program Festival Anak Sholeh sebagai Strategi Penguatan Pendidikan Karakter Islami Anak di Desa Lubuk Ruso Kecamatan Pemayung Kabupaten Batang Hari - Ahmadal Hadi; Farah Farida; Fitri Lestari; Hikmatul Ulya; Safna Safira Rizkiyah; M. Yusuf (Medan Resource Center, 2026)
The Festival Anak Sholeh represents a community-based religious initiative that functions as a non-formal educational medium to foster Islamic character values among children in rural settings. This study investigates how the program is implemented and examines its effectiveness as a strategy for strengthening Islamic character education among elementary school-aged participants. Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation involving community service students, religious leaders, village officials, organizing committee members, and child participants in Lubuk Ruso Village, Pemayung District, Batang Hari Regency. The findings reveal that the program significantly enhances children’s motivation to learn religious knowledge, strengthens self-confidence, and improves public performance skills, particularly in adhan recitation, Qur’anic tilawah, and memorization of short surahs. The program also contributes to the internalization of religious values such as discipline, responsibility, and confidence, supported by strong community engagement and the active role of local religious figures. This study argues that the Festival Anak Sholeh constitutes an effective and contextually relevant strategy for reinforcing Islamic character education, despite constraints related to limited facilities and time allocation.